Left Ventricular Systolic Dysfunction and the Risk of Ischemic Stroke in a Multiethnic Population - Hays, Allison G. (2006)
BACKGROUND AND PURPOSE: Left ventricular dysfunction (LVD) is associated with cardiovascular mortality. Its association with ischemic stroke has been mainly documented after myocardial infarction. The stroke risk associated with LVD, especially of mild degree, in the general population is unclear. The purpose of this study was to evaluate the relationship between LVD and ischemic stroke in a multiethnic cohort. METHODS: LV systolic function was assessed by transthoracic 2-dimensional echocardiography in a subset of subjects from the Northern Manhattan Study (NOMAS), 270 patients with first ischemic stroke and 288 age-, gender- and race-matched community controls. LV ejection fraction was measured by a simplified cylinder-hemiellipsoid formula, and categorized as normal (>50%), mildly (41% to 50%), moderately (31% to 40%) or severely (≤30%) decreased. The association between impaired ejection fraction and ischemic stroke was evaluated by logistic regression analysis after adjustment for established stroke risk factors. RESULTS: LVD of any degree was more frequent in stroke patients (24.1%) than in controls (4.9%; P<0.0001), as was moderate/severe LVD (13.3% versus 2.4%; P<0.001). A decreased ejection fraction was associated with ischemic stroke even after adjusting for other stroke risk factors. The adjusted odds ratio for any degree of LVD was 3.92 (95% CI, 1.93 to 7.97). The adjusted odds ratio for mild LVD was 3.96 (95% CI, 1.56 to 10.01) and for moderate/severe LVD 3.88 (95% CI, 1.45 to 10.39). The association between LVD of any degree and stroke was present in all age, gender and race-ethnicity subgroups. CONCLUSIONS: LVD, even of mild degree, is independently associated with an increased risk of ischemic stroke. The assessment of LV function should be considered in the assessment of the stroke risk.